Atmospheric CO2 at Waliguan station in China: Transport climatology, temporal patterns and source-sink region representativeness. (June 2017) - Cheng, Siyang; An, Xingqin; Zhou, Lingxi; Tans, Pieter P.; Jacobson, Andy
Abstract: In order to explore where the source and sink have the greatest impact on CO2 background concentration at Waliguan (WLG) station, a statistical method is here proposed to calculate the representative source-sink region. The key to this method is to find the best footprint threshold, and the study is carried out in four parts. Firstly, transport climatology, expressed by total monthly footprint, was simulated by FLEXPART on a 7-day time scale. Surface CO2 emissions in Eurasia frequently transported to WLG station. WLG station was mainly influenced by the westerlies in winter and partly controlled by the Southeast Asian monsoon in summer. Secondly, CO2 concentrations, simulated by CT2015, were processed and analyzed through data quality control, screening, fitting and comparing. CO2 concentrations displayed obvious seasonal variation, with the maximum and minimum concentration appearing in April and August, respectively. The correlation of CO2 fitting background concentrations was R 2  = 0.91 between simulation and observation. The temporal patterns were mainly correlated with CO2 exchange of biosphere-atmosphere, human activities and air transport. Thirdly, for the monthly CO2 fitting background concentrations from CT2015, a best footprint threshold was found based on correlation analysis and numerical iteration using the data of footprints and emissions. The grid cells where monthly footprints were greater than the best footprint threshold were the best threshold area corresponding to representative source-sink region. The representative source-sink region of maximum CO2 concentration in April was primarily located in Qinghai province, but the minimum CO2 concentration in August was mainly influenced by emissions in a wider region. Finally, we briefly presented the CO2 source-sink characteristics in the best threshold area. Generally, the best threshold area was a carbon sink. The major source and sink were relatively weak owing to less human activities and vegetation types in this high altitude area. CO2 concentrations were more influenced by human activities when air mass passed through many urban areas in summer. Therefore, the combination of footprints and emissions is an effective approach for assessing the source-sink region representativeness of CO2 background concentration. Highlights: The transport climatology at Waliguan station in China was obtained by total monthly footprint. CO2 background values were extracted from simulations, and temporal patterns thereof were compared with observations. A method is proposed to explore where the sources and sinks have the greatest impact on CO2 background concentrations. The sources and sinks were analyzed in the representative source-sink regions of the monthly CO2 background concentrations.